Una nueva especie de Hymenophyllum y una variedad nueva de Trichomanes collariatum Bosch (Filicales: Hymenophyllaceae) en Costa Rica - Rojas Alvarado, Alexander (Lankesteriana: International Journal on Orchidology, 2015)
A new species and a new variety of Hymenophyllaceae are described for Costa Rica. Hymenophyllum talamancanum, somewhat similar to H. horizontale C. V. Morton, and Trichomanes collar- iatum Bosch var. alvaradoi, with some differences compared to the typical variety.